Transmurally migrated gossypiboma rarely posing as surgical site infection: a case report and review of literature - Gaurav, Amrita; Mishra, Juhi; Kumari, Om; Khoiwal, Kavita; Huda, Farhanul; Chaturvedi, Jaya (International Surgery Journal, 2020)
The term gossypiboma is used to describe a retained surgical sponge or gauge after surgery. The clinical features range from being asymptomatic to frank bowel obstruction, perforation and peritonitis. Radiological modalities also do not provide a definite diagnosis. We report a case of a 30-year-old lady who presented to the emergency room with recurrent surgical site infection. She had a history of caesarean section 5 months ago. Following the caesarean section, she developed superficial wound dehiscence which was re-sutured. At the present facility, the lady underwent Computed tomography (CT) scan and was suspected to have a foreign body around the gut. She was planned for an exploratory laparotomy. Upon laparotomy, a large thick-walled ileal loop with some unusual intra luminal mass was found. Dense adhesions were present between the ileal loop and sigmoid colon. Adhesiolysis led to an iatrogenic sigmoid colon perforation, around 2 cm length. On incision over the ileal loop, surgical sponge was retrieved. Ileal loop was resected along with perforated site with end-to-end ileo-ileal anastomosis was done. Primary repair of sigmoid colon perforation was done. Patient was stable in postoperative period. Although rare, gossypiboma should be kept in mind as a differential diagnosis in postoperative cases presenting with recurrent surgical site infection.